2020
DOI: 10.1177/1948550620948973
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Extension of Alicke (1985) Better-Than-Average Effect for Desirable and Controllable Traits

Abstract: People tend to regard themselves as better than average. We conducted a replication and extension of Alicke’s classic study on trait dimensions in evaluations of self versus others with U.S. American Mechanical Turk workers in two waves (total N = 1,573; 149 total traits). We successfully replicated the trait desirability effect, such that participants rated more desirable traits as being more descriptive of themselves than of others (original: [Formula: see text] = .78, 95% confidence interval [CI] [.73, .81]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In line with this reasoning, the BTAE is especially strong for traits that are both personally (Brown, 2012; Ziano et al, 2020) and socially/culturally important (Lee, 2012; Sedikides et al, 2003). This bias also increases in magnitude after participants experience a threat to their feelings of self-worth (Brown, 2012), which indicates that it is responsible for protecting one’s self-esteem.…”
Section: Comparing With Others In a Moment Of Crisis: Better-than-ave...mentioning
confidence: 88%
“…In line with this reasoning, the BTAE is especially strong for traits that are both personally (Brown, 2012; Ziano et al, 2020) and socially/culturally important (Lee, 2012; Sedikides et al, 2003). This bias also increases in magnitude after participants experience a threat to their feelings of self-worth (Brown, 2012), which indicates that it is responsible for protecting one’s self-esteem.…”
Section: Comparing With Others In a Moment Of Crisis: Better-than-ave...mentioning
confidence: 88%
“…Recently, Ziano et al (2020) conducted a replication of another classic study on the better-thanaverage effect (Alicke, 1985), which indicated that college students' ratings of how characteristic a trait was of them (vs. an average student) increased with increasing desirability of the trait, and that this effect was stronger among more controllable traits. Findings from Ziano et al (2020) were consistent with the original findings. In sum, findings from the present study are in line with the view of the better-than-average effect as a robust phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This project, which involves students conducting collaborative studies with hands-on support, has resulted in 20 peer-reviewed publications (e.g. see Brick et al, 2021;Chandrashekar et al, 2021;Ziano et al, 2021). In student evaluations of this project (Feldman, 2021), a student wrote "I learned a lot about designs of experiments, adding extensions to them, as well as the impact of replications.…”
Section: Students' Understanding Of Open Researchmentioning
confidence: 99%